Branching angles of several cocoa genotypes and their effect on determining optimum plant spacing - Bayu Setyawan; Indah Anita-Sari; Fatrezza Ihsan; Heksan Panua (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2021)
Identification of the type of branching architecture will be one for the considerations in determining specific spacing recommendations for cocoa plantation. The research was conducted at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute. The aim of this study was to investigate of branching angle characteristics of cocoa clones that can be used in determining planting space in cocoa farms. This research usied a completely randomized block design (RCBD) consisting of 21 genotypes as treatments. Each treatment was repeated three times and each replication consisted of three sample plants. Parametersobserved were branch angle and the type of branching. Branch angle is the angle formed by the outermost primary branch and was measured using a protractor. The results showed that each genotype had a different angle on the primary branch, while the secondary and tertiary branch angles did not shown any significantdifference. The results of the analysis showed that of the 21 genotypes tested, ICCRI 03, BAL 209, and KW 411 showed horizontal branching type; Sulawesi 1 and Sulawesi 3 showed vertical branching type, while the other 16 genotypes had intermediate branching types. Cocoa clones with a vertical branching type can be planted in denser spacing compared to cocoa clones with a horizontal branching type. The population per hectare of clones with vertical branching type can be increased 3 to 4 times when compared to clones with horizontal branching type.